Mcl-1 Is a Novel Target of miR-26b That Is Associated with the Apoptosis Induced by TRAIL in HCC Cells. (21st May 2015) - Jiang, Chunlin; Long, Jianting; Liu, Baoxian; Xie, Xiaoyan; Kuang, Ming
Abstract : Aim . To investigate the role of miR-26b and Mcl-1 in TRAIL-inducing cell death in hepatocellular carcinoma. Methods . The expression of miR-26b and Mcl-1 in HCC was detected by RT-qPCR and western blot. The regulation of Mcl-1 by miR-26b was determined by luciferase reporter assay. MTT and flow cytometry were employed to detect the cell viability and apoptosis. Results . miR-26b is commonly downregulated in HCC cell lines compared with the LO2 cell line. In contrast, the Mcl-1 expression is upregulated in HCC cell lines. Bioinformatic analysis identified a putative target site in the Mcl-1 mRNA for miR-26b and luciferase reporter assay showed that miR-26b directly targeted the 3′-UTR (3′-Untranslated Regions) of Mcl-1 mRNA. Transfection of miR-26b mimics suppressed Mcl-1 expression in HCC cells and sensitized the cancer cells to TRAIL (tumor necrosis factor-related apoptosis-inducing ligand) cytotoxicity. In addition, transfection of HCC cells with Mcl-1 expression plasmid abolished the sensitization effect of miR-26b to TRAIL-inducing apoptosis. Conclusions . Our study showed that miR-26b was a negative regulator of Mcl-1 gene and sensitized TRAIL-inducing apoptosis in HCC cells, suggesting that the miR-26b-Mcl-1 pathway might be a novel target for the treatment of HCC.